Pengaruh Penggunaan Aplikasi Filmora Terhadap Hasil Belajar Pada Mata Pelajaran Editing Video Siswa Kelas XI SMK Negeri 2 Bone - Muh. Alfian Iqbal; Jusman Jusman (Peneliti.net, 2023)
This study aims to determine the effect of using the Filmora application on student learning outcomes in the video editing subject for SMK Negeri 2 Bone class XI students. The research used is quantitative research with the type of Experimental Design research with the One Group Pre-Test and Post-Test Design type. The total population is all class XI Multimedia with a total of 30 students. The sample in this study amounted to 30 people. The data collection technique used in this study was the provision of learning achievement tests (Pre-Test and Post-Test), documentation and observation. The results of the descriptive analysis were carried out by looking at the results of the acquisition of student learning outcomes tests through the provision of test instruments. Based on the results of the analysis obtained using the SPSS Version 23 application, the average value of student learning outcomes before using the media (Pre-Test) is at an interval of 40-54 where the value is categorized as low while the average value of student learning outcomes after being treated using the media The Filmora application (Post-Test) is already in the interval 75 – 89 where the value is categorized as high. Furthermore, the results of inferential analysis were carried out using the SPSS Version 23 application. The normality and homogeneity test results obtained normal and homogeneous data results. While the hypothesis testing was carried out using paired sample pre-test post-test, the significance value was less than 0.05, which was 0.000, where sig (2-tailed) <0.05. This proves that there is a significant influence between the two variables used. The study's conclusion shows a positive effect on the use of the Filmora Application on Learning Outcomes in the Video Editing Subject for Class XI Students of SMK Negeri 2 Bone.